Revisão bibliográfica da seletividade de Diamidas utilizados em cana-de-açúcar sobre Cotesia flavipes e Trichogramma galloi - Nalhato, Paulo Henrique (Universidade Federal de São Carlos, 2021)
The sugarcane borer (Diatraea saccharalis) is an important pest in one of the most important crops for the Brazilian scenario: sugar cane. Nevertheless, the unbridled use of phytosanitary products has generated necessary debates about their association with the effectiveness of biological control, since several products do not have selectivity for beneficial organisms such as T. galloi and C. flavipes in agroecosystems. However, recent discoveries have shown that the chemical group Diamidas can be an alternative for the correct application of Integrated Pest Management, since this group has been shown to be selective to the natural enemies of the sugarcane borer, ensuring the maintenance of the populations of these organisms in the agro-ecosystem and enabling biological control in Brazilian sugarcane fields. Therefore, this study aims to study the selectivity of insecticides from the chemical group diamides at different stages of development of Cotesia flavipes and Trichogramma galloi, through the literature review.
Literature review of the selectivity of Diamides used in sugarcane on Cotesia flavipes and Trichogramma galloi
Keywords: Inimigos naturais; Controle biológico; Controle químico; CIENCIAS AGRARIAS::AGRONOMIA